TRADISI BARONGSAI DI MATA MUSLIM TIONGHOA: MENYANDINGKAN KEBERISLAMAN DAN KETIONGHOAAN - Moch. Choirul Arif; Simatupang; Budiawan (Al'Adalah, 2015)
Post-published Decree No. 6 of 2000 by President KH. Abdurrahman Wahid suspend the number 14 of 1967 on religion, beliefs and customs of the Chinese, is an important moment for Indonesian ethnic Chinese community represents their cultural identity. Emergence Lion Dance tradition in the public sphere becomes a marker of cultural freedom that has long shackled due to political discrimination of the New Order. As an icon of cultural freedom, the Lion Dance in glasses Confucianism is perceived as a symbol of bravery and unyielding and human compulsion to clean ourselves from all forms of malicious behavior. and considered able to reconcile between the profane with the sacred, so is able to connect people with the unseen. Although the substance is good, but leaves a theological problem for the Chinese Muslim community.Through two-way translation strategy played PITI organization, the Chinese Muslim community is able to reconcile Islam with Chineseness. Islam yes, the Chinese also yes.